2020
DOI: 10.3390/ijms21249652
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA Damage, Inflammatory Signature, and Altered Erythrocytes Properties in Diamond-Blackfan Anemia

Abstract: Molecular pathophysiology of Diamond-Blackfan anemia (DBA) involves disrupted erythroid-lineage proliferation, differentiation and apoptosis; with the activation of p53 considered as a key component. Recently, oxidative stress was proposed to play an important role in DBA pathophysiology as well. CRISPR/Cas9-created Rpl5- and Rps19-deficient murine erythroleukemia (MEL) cells and DBA patients’ samples were used to evaluate proinflammatory cytokines, oxidative stress, DNA damage and DNA damage response. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…As mentioned above, in addition to ribosomal stress, p53 could be activated by HEMmediated ROS production [60,61]. Although it has been reported that GCs reduce ROS species [62][63][64], their overall influence on ROS production is ambiguous [65].…”
Section: Regulation Of Ribosomal Stress and P53mentioning
confidence: 97%
See 2 more Smart Citations
“…As mentioned above, in addition to ribosomal stress, p53 could be activated by HEMmediated ROS production [60,61]. Although it has been reported that GCs reduce ROS species [62][63][64], their overall influence on ROS production is ambiguous [65].…”
Section: Regulation Of Ribosomal Stress and P53mentioning
confidence: 97%
“…More specifically, it seems that short-term GC usage leads to a reduction in ROS generation, whereas long-term exposure leads to ROS induction [65]. Furthermore, increased ROS levels have been detected in DBA patients regardless of treatment [60]. Therefore, GC-mediated p53 regulation does not seem to reflect ROS levels.…”
Section: Regulation Of Ribosomal Stress and P53mentioning
confidence: 98%
See 1 more Smart Citation
“…Whether cytokines are drivers or passengers in BMF development is still an open question. Indeed, prolonged in vitro exposure to TNFα and IFNγ can induce senescence through increased oxidative stress, reactive oxygen species (ROS) production, and DNA damage, as also recently described in DBA [145,146]. Oxidative stress and DNA damage are generated by IL1β and TGFβ persistent stimulation.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, damaged or mutated ribosomal proteins can mediate oxidative stress. It has been demonstrated that increased levels of reactive oxygen species (ROS) have been detected in RPL5-and RPS19-de cient Diamond-Blackfan anemia (DBA) mouse cell models [37]. Thus, the disruption of ribosome assembly increases ROS production, thereby leading to an oxidative and translational defective cellular "snowball" effect that may further enhance the mutagenic phenotype [34].…”
Section: Hypothesis On the Mechanisms Of Ribosomal Involvement In Dox...mentioning
confidence: 99%